From Diagnosis to Health Practice: Polycythemia Vera. A Literature Review - Katarzyna Siekaniec; Bartosz Roś; Natalia Kuchenbeker; Adriana Dojs; Julia Mierzwińska-Mucha; Magdalena Jakubowicz; Wojciech Kowalewski (Journal of Education, Health and Sport)
Introduction and purpose: Polycythemia vera (PV) is a chronic myeloproliferative neoplasm, part of the group of Philadelphia-negative neoplasms alongside essential thrombocythemia and myelofibrosis. It is characterized by elevated red blood cell mass, frequently accompanied by leukocytosis and thrombocytosis. A JAK2 mutation is present in about 95% of cases, typically with low erythropoietin levels. This study aims to review the current understanding of PV, including its pathophysiology, diagnostic criteria, treatment options, and emerging therapies.